Characteristics of climbers of Gunung Tahan, Taman Negara National Park, Pahang, Malaysia - Yaakob, Sam Shor Nahar; Mohamed, Shukri (Forestry Department Peninsular Malaysia, 2017)
The objectives of this paper are to present the profile and motives of the climbers to Gunung Tahan’s summit. The respondents, recruited during an on-site and off-site survey, were asked to provide some socio-demographic characteristics, their previous mountain climbing experiences and motives for trekking up the summit by filling up a self-administered questionnaire. Novice climbers formed the majority of the 336 respondents recruited during the survey, followed by experienced climbers and mountain guides. Most of the respondents were young adult males, especially students from the local universities. The respondents rated the “to be close to nature” motive as the most important reason for trekking up the summit of Gunung Tahan.